Contribuição para o estudo da vinha e do vinho dos Açores - Medeiros, Carlos Alberto (1994)
VINE GROWING AND WINE PRODUCTION IN THE AZORES - The cultivation of vines in the Azores dates back to the first settlers. It was particularly significant in Pico and São Jorge where better quality wine was produced; however the wine exported from the archipelago was generally not of financial importance. On the islands of Faial, Flores and Corvo the wine was always a minor or absent culture.This paper focuses the evolution of the vines from early times to the present day, its significance in rural landscape and in the economy of the Azores. From mid-nineteenth century the vines, proceeding from Europe, were attacked by plagues of oidium and phylloxera. The European vines were subsequently replaced in nearly all the areas by the american variety called "Isabela" (Vitis labrusca, L.). The "vinho de cheiro" (known as foxy to the Americans) which was produced, was of inferior quality; however it was easily assimilated into the diet of the islanders. The E.C. legislation foresees a progressive replacement of the "Isabela". This replacement process will be slow and dificult. Nowadays the area of vine cultivation (very parcelled) does not exceed 2500 or 3000 hactares. The main vine area is located on the island of Pico (more than 900 hectares); this is the only island on which grows a significant amount of European vine. On the island of São Miguel (the largest island) only the American vine is grown.